Synthetic tsunami waveform catalogs with kinematic constraints - Baptista, Maria Ana Carvalho Viana (2017)
In this study we present a comprehensive methodology to produce a synthetic tsunami waveform catalogue in the northeast Atlantic, east of the Azores islands. The method uses a synthetic earthquake catalogue compatible with plate kinematic constraints of the area. We use it to assess the tsunami hazard from the transcurrent boundary located between Iberia and the Azores, whose western part is known as the Gloria Fault. This study focuses only on earthquake-generated tsunamis. Moreover, we assume that the time and space distribution of the seismic events is known. To do this, we compute a synthetic earthquake catalogue including all fault parameters needed to characterize the seafloor deformation covering the time span of 20 000 years, which we consider long enough to ensure the representability of earthquake generation on this segment of the plate boundary. The computed time and space rupture distributions are made compatible with global kinematic plate models. We use the tsunami empirical Green's functions to efficiently compute the synthetic tsunami waveforms for the dataset of coastal locations, thus providing the basis for tsunami impact characterization. We present the results in the form of offshore wave heights for all coastal points in the dataset. Our results focus on the northeast Atlantic basin, showing that earthquake-induced tsunamis in the transcurrent segment of the Azores-Gibraltar plate boundary pose a minor threat to coastal areas north of Portugal and beyond the Strait of Gibraltar. However, in Morocco, the Azores, and the Madeira islands, we can expect wave heights between 0.6 and 0.8 m, leading to precautionary evacuation of coastal areas. The advantages of the method are its easy application to other regions and the low computation effort needed.